Isolation and characterisation of lignin using natural deep eutectic solvents pretreated kenaf fibre biomass - Meraj, Aatikah; Jawaid, M.; Singh, Surendra Pratap; Nasef, Mohamed Mahmoud; Ariffin, Hidayah; Fouad, Hassan; Abu‐Jdayil, Basim (Nature Research, 2024)
Extraction of lignin via green methods is a crucial step in promoting the bioconversion of lignocellulosic biomasses. In the present study, utilisation of natural deep eutectic solvent for the pretreatment of kenaf fibres biomass is performed. Furthermore, extracted lignin from natural deep eutectic solvent pretreated kenaf biomass was carried out and its comparative study with commercial lignin was studied. The extracted lignin was characterized and investigated through Infrared Fourier transform spectroscopy, X-ray Diffraction, thermogravimetric analysis, UV–Vis spectroscopy, and scanning electron microscopy. FTIR Spectra shows that all samples have almost same set of absorption bands with slight difference in frequencies. CHNS analysis of natural deep eutectic solvent pretreated kenaf fibre showed a slight increase in carbon % from 42.36 to 43.17% and an increase in nitrogen % from − 0.0939 to − 0.1377%. Morphological analysis of commercial lignin shows irregular/uneven surfaces whereas natural deep eutectic solvent extracted lignin shows smooth and wavy surface. EDX analysis indicated noticeable peaks for oxygen and carbon elements which are present in lignocellulosic biomass. Thermal properties showed that lignin is constant at higher temperatures due to more branching and production of extremely condensed aromatic structures. In UV–VIS spectroscopy, commercial lignin shows slightly broad peak between 300 and 400 nm due to presence of carbonyl bond whereas, natural deep eutectic solvent extracted lignin does not show up any peak in this range. XRD results showed that the crystallinity index percentage for kenaf and natural deep eutectic solvent treated kenaf was 70.33 and 69.5% respectively. Therefore, these innovative solvents will undoubtedly have significant impact on the development of clean, green, and sustainable products for biocatalysts, extraction, electrochemistry, adsorption applications. © The Author(s) 2024.